FORMAL FEATURES AND PARAMETER SETTING: A VIEW FROM PORTUGUESE PAST PARTICIPLES AND ROMANCE FUTURE TENSES - Lobato, Lucia (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This paper examines the morphophonological shape of Portuguese past participles, including the stress placement change that took place from Latin to Portuguese in these forms, and argues for a concept of formal feature more abstract than the concept of morphosyntactic feature. Parameter setting is treated as relating to the location in which the configuration of formal features relevant to grammatical semantic interpretation is visible to the PF system. The stages in the development of the Romance future tenses are claimed to follow from a shift in the visibility of the sentential functional heads